Saliva phosphorylated tau concentration is not associated with Alzheimer’s disease, cerebrospinal fluid or blood biomarkers - Gleerup, Helena Sophia; Sanna, Federica; Koutarapu, Srinivas; Lantero-Rodriguez, Juan; Montoliu-Gaya, Laia; Hanrieder, Jörg; Brinkmalm, Gunnar; Karikari, Thomas K.; Simren, Joel; Høgh, Peter; Blennow, Kaj; Hasselbalch, Steen Gregers; et al. (Frontiers in Neuroscience, 2025)
ObjectiveOne of the most challenging aims of the scientific community in the last decade, is to find an easily accessible matrix in which neurodegeneration-related biomarkers can be measured and used to diagnose Alzheimer’s disease (AD) in vivo. Blood biomarkers have led the way in this regard, specifically, phosphorylated tau (p-tau) which demonstrates excellent diagnostic and prognostic properties. The recent success of the blood biomarkers for AD pathophysiology poses a new question – can p-tau be measured in other peripheral and even more accessible biofluids, and do they have relation to disease? Saliva contains biomarkers linked to neurodegeneration and it has been proposed as a potential sample type that would be minimally invasive to collect for this purpose.MethodsIn this study, we confirmed the presence of several p-tau species in saliva fluid and saliva gland tissue by Immunoprecipitation-Mass spectrometry (IP-MS) and immunohistochemistry, respectively. Furthermore, we measured saliva and plasma p-tau181 concentrations in 125 memory clinic participants, using ultrasensitive Single molecule array (Simoa) technology.ResultsDespite a weak correlation between saliva p-tau181 and CSF t-tau (rho = 0.13, p < 0.01), there were no significant differences in saliva p-tau181 concentration between the different clinical groups and the healthy controls.InterpretationFor this reason, we conclude that saliva p-tau181 is not acceptable as a biomarker for AD.